2021
DOI: 10.3389/fvets.2020.609518
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Profiling of Buffalo Spermatozoa Reveals Dysregulation of Functionally Relevant mRNAs in Low-Fertile Bulls

Abstract: Although, it is known that spermatozoa harbor a variety of RNAs that may influence embryonic development, little is understood about sperm transcriptomic differences in relation to fertility, especially in buffaloes. In the present study, we compared the differences in sperm functional attributes and transcriptomic profile between high- and low-fertile buffalo bulls. Sperm membrane and acrosomal integrity were lower (P < 0.05), while protamine deficiency and lipid peroxidation were higher (P < 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 76 publications
1
24
0
Order By: Relevance
“…Recently, it was shown that a lower level of the microRNA miR-216b in bovine spermatozoa and zygotes was associated with a higher level of K-RAS (a gene of the RAS/MAPK pathway) in two-cell embryos, which increased first cleavage rate and blastocyst cell numbers from bulls with high fertility, while the opposite was for low fertility bulls [ 53 ]. Similarly, transcriptomic profiling of buffalo spermatozoa revealed downregulation of 28 genes associated with MAPK signaling pathway bulls with low fertility compared to those with high fertility [ 54 ]. Thus the enhanced fertilization ability and embryo development observed in our study could hypothetically be linked to this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that a lower level of the microRNA miR-216b in bovine spermatozoa and zygotes was associated with a higher level of K-RAS (a gene of the RAS/MAPK pathway) in two-cell embryos, which increased first cleavage rate and blastocyst cell numbers from bulls with high fertility, while the opposite was for low fertility bulls [ 53 ]. Similarly, transcriptomic profiling of buffalo spermatozoa revealed downregulation of 28 genes associated with MAPK signaling pathway bulls with low fertility compared to those with high fertility [ 54 ]. Thus the enhanced fertilization ability and embryo development observed in our study could hypothetically be linked to this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Although differences in opinion exist about the transcription and translation activities in spermatozoa, it was observed that paternal RNAs reside in the perinuclear theca of spermatozoa and are transferred during fertilization ( Ostermeier et al, 2005 ). Recent studies profiled sperm RNA and the possible roles in sperm functions and fertilizing ability ( Selvaraju et al, 2017 ; Paul et al, 2020 ; Prakash et al, 2020 ). Increasing evidence indicates that expression of sperm molecules, including mRNAs ( Wang et al, 2019 ; Saraf et al, 2021 ; Selvaraju et al, 2021 ), proteins ( Peddinti et al, 2008 ; Aslam et al, 2015 ), phosphoproteins ( Kumaresan et al, 2012 ), and metabolites ( Saraf et al, 2020 ), were altered in bulls with different fertility ratings.…”
Section: Compounding Factors For Infertility/sub-fertility In Crossbred Bullsmentioning
confidence: 99%
“…This novel technique is now widely used on animals for large-scale gene expression studies involving SNP genotyping, polymorphisms, disease diagnosis, fertility assay etc. [59][60][61][62][63][64].…”
Section: Microarray Technologymentioning
confidence: 99%
“…Another study demonstrated transcriptional analysis of potential buffalo genes that are associated with buffalo oocyte maturation using the microarray technology [62]. Very recently, microarray technology had also been used to analyze the transcriptomic profile of buffalo spermatozoa that report the alteration of functionally relevant transcripts in low-fertile bull spermatozoa [63]. Thus, microarray technology can allow animal geneticists and breeders to select animals based on multiple traits and hopefully can revolutionize the buffalo production and breeding industry.…”
Section: Microarray Technologymentioning
confidence: 99%